2022
DOI: 10.3390/ijms23031070
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Insights on the Diverse Roles of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) in Chronic Liver Diseases: Cholesterol Metabolism and Beyond

Abstract: Chronic liver diseases are commonly associated with dysregulated cholesterol metabolism. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease of the proprotein convertase family that is mainly synthetized and secreted by the liver, and represents one of the key regulators of circulating low-density lipoprotein (LDL) cholesterol levels. Its ability to bind and induce LDL-receptor degradation, in particular in the liver, increases circulating LDL-cholesterol levels in the blood. Hence, inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 181 publications
(341 reference statements)
3
16
0
Order By: Relevance
“…From the present study, it is clear that both total lipids and total cholesterol were increased by induction of T2 toxin; therefore, by treatment with taurine, the level of them decreased significantly, but curcumin exhibited a fabulous effect more than taurine in decreasing total lipid and cholesterol. This study agrees with other studies that found that mycotoxin levels are linked to hypercholesterolemia and has a negative impact on liver cholesterol metabolism via cholesterol production ( Anyanwu et al, 2006 ; Martins, 2015 ; Grewal and Buechler, 2022 ). In human and animal plasma, mycotoxins have been found to attach to lipoproteins and cause hypercholesterolemia ( Martins, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…From the present study, it is clear that both total lipids and total cholesterol were increased by induction of T2 toxin; therefore, by treatment with taurine, the level of them decreased significantly, but curcumin exhibited a fabulous effect more than taurine in decreasing total lipid and cholesterol. This study agrees with other studies that found that mycotoxin levels are linked to hypercholesterolemia and has a negative impact on liver cholesterol metabolism via cholesterol production ( Anyanwu et al, 2006 ; Martins, 2015 ; Grewal and Buechler, 2022 ). In human and animal plasma, mycotoxins have been found to attach to lipoproteins and cause hypercholesterolemia ( Martins, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the association between serum cholesterol and PCSK9 levels is lacking, which may be due to the overriding effect of PCSK9 on cholesterol metabolism. Lower PCSK9 levels in patients with liver disease are associated with reduced levels of pro-inflammatory factors, suggesting a reduction in the occurrence of atherosclerotic events ( 117 ). In a previous study, serum PCSK9 levels and the international normalized ratio were shown to be negatively associated with each other, suggesting a higher risk of bleeding ( 118 ).…”
Section: Roles Of Pcsk9 In Thrombosis and Haemostasis Under Disease S...mentioning
confidence: 99%
“…Statins are widely prescribed drugs effectively lowering systemic LDL-cholesterol levels ( Grewal & Buechler, 2022 ) that also substantially reduce cholesterol levels at the plasma membrane. The latter disturbs the formation of cholesterol-rich microdomains, and lipophilic statins (e.g., lovastatin, simvastatin, pitavastatin, atorvastatin) probably displace ACE2 from cholesterol-rich lipid rafts, which reduces its ability to serve as SARS-CoV-2 receptor ( Bakillah et al, 2022 ; Fiore et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides statins, inhibitory antibodies against proprotein convertase subtilisin/kexin type 9 (PCSK9) are now used to treat hypercholesterinemia, increasing LDL receptor levels at the cell surface for enhanced LDL clearance ( Sundararaman et al, 2021 ; Grewal & Buechler, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation